2007
DOI: 10.1155/2007/35378
|View full text |Cite
|
Sign up to set email alerts
|

Variationally Asymptotically Stable Difference Systems

Abstract: We characterize the h-stability in variation and asymptotic equilibrium in variation for nonlinear difference systems via n ∞ -summable similarity and comparison principle. Furthermore we study the asymptotic equivalence between nonlinear difference systems and their variational difference systems by means of asymptotic equilibria of two systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The notion of similarity is an effective tool to study the theory of stability for differential systems and difference systems [5,7,10,11,12,17,18,19]. Markus [17] introduced the notion of kinematic similarity in the set of all n × n continuous matrices defined on [t 0 , ∞) and showed that the relationship of kinematic similarity is an equivalence relation preserving the type numbers of the linear differential systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of similarity is an effective tool to study the theory of stability for differential systems and difference systems [5,7,10,11,12,17,18,19]. Markus [17] introduced the notion of kinematic similarity in the set of all n × n continuous matrices defined on [t 0 , ∞) and showed that the relationship of kinematic similarity is an equivalence relation preserving the type numbers of the linear differential systems.…”
Section: Introductionmentioning
confidence: 99%
“…Trench [19] introduced summable similarity as a discrete analog of Conti's definition of t ∞ -similarity and investigated the various stabilities of linear difference systems by using summable similarity. Choi et al [5] studied the asymptotic property and the h-stability of difference systems via discrete similarities and comparison principle. For detailed results about the various stabilities including the notions of h-stability and strong stability of dynamic systems on time scales, see [6,8].…”
Section: Introductionmentioning
confidence: 99%